2014
DOI: 10.2139/ssrn.2585239
|View full text |Cite
|
Sign up to set email alerts
|

Financial Knowledge and 401(K) Investment Performance

Abstract: At least one co-author has disclosed a financial relationship of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w20137.ack NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Similarly, Kim et al (2005) found that attending financial education workshops was positively related to both employees' and their spouses' contributions to retirement savings plans. Clark et al (2014) explored associations between financial knowledge and retirement savings plan performance and found that risk-adjusted annual expected returns were 130 basis points higher for the most financially knowledgeable employees.…”
Section: Impact Of Financial Education On Financial Capabilitymentioning
confidence: 99%
“…Similarly, Kim et al (2005) found that attending financial education workshops was positively related to both employees' and their spouses' contributions to retirement savings plans. Clark et al (2014) explored associations between financial knowledge and retirement savings plan performance and found that risk-adjusted annual expected returns were 130 basis points higher for the most financially knowledgeable employees.…”
Section: Impact Of Financial Education On Financial Capabilitymentioning
confidence: 99%
“…For instance, Allen et al () assessed employer‐provided retirement seminars and showed that these seminars boosted financial literacy and influenced people's ability to plan for retirement . In our previous research (Clark, Lusardi, and Mitchell ; Lusardi, Michaud, and Mitchell ), we examined whether financial literacy is linked to investment returns and we found that more financially literate employees are better investors. Moreover, the higher returns earned by the more financially savvy are an important contributor to household wealth inequality.…”
Section: Introductionmentioning
confidence: 95%
“…A more detailed analysis of how financial literacy influences the investment behavior and portfolio allocation of FR employees is available in Clark, Lusardi, and Mitchell (). This analysis shows that individuals with higher levels for financial literacy tend to have less idiosyncratic risk and earn higher expected risk‐adjusted returns.…”
mentioning
confidence: 99%
“…A more detailed analysis of how financial literacy influences portfolio outcomes is taken up inClark, Lusardi and Mitchell (2014).…”
mentioning
confidence: 99%